Genetics of Lung Cancer - Etem, Ebru Onalan (Bentham Science Publ, 2013)
Lung cancer is developed through the accumulation of genetic alterations. The number of potential lung cancer-related genes have been enlightened over the last 20 years. Several molecular genetic abnormalities have been described in the pathogenesis of lung cancer, including the mutational activations of oncogenes, the inactivation of tumour suppressor genes and the alterations in the genes responsible for cell cycle regulation and DNA repair. Lung cancer progression is characterised by cumulative alterations in key molecules involved in the cell cycle, signaling and angiogenesis pathways. The identification of developmentally regulated pathways active in tumourigenesis provides insights into lung carcinogenesis and suggests early steps may differ according to the eventual tumour morphology. Developing novel biological agents to target lung cancer, and new microarray-based technologies provide new methods for predicting prognosis and response to treatment. In this chapter, particulars that have been focus on major recent advances in the molecular study of the origins and biology of lung cancer.
Keywords: Lung cancer; cytogenetic; molecular genetic; signaling mechanism; oncogene; tumour suppressor gene